2023
DOI: 10.22495/cgobrv7i3p4
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of stock returns to asymmetric changes in exchange rates and oil prices

Abstract: When an economy does well as a result of crude oil proceeds, it is expected that its financial market records a boost. So, when the economy regresses due to fluctuations in oil prices, its financial market also reacts in tandem. To shed light on the uninterrupted fluctuations, we empirically estimated the effect of changes in exchange rates and oil prices on stock returns in developing countries using the nonlinear autoregressive distributed lag (NARDL) methodology. Results reveal that a 1 percent negative sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
0
0
0
Order By: Relevance
“…Dahir et al (2018) observed similar asymmetry across the BRICS countries, with positive impacts in Brazil and Russia, negative impacts in India, and a bidirectional relationship in South Africa. Gokmenoglu et al (2021) and Umoru et al (2023) also suggest that the response of stock returns to exchange rate fluctuations is not uniform in emerging economies and in oil-producing African countries, respectively. Amewu et al (2022) observed that the Covid-19 pandemic significantly altered the relationship between exchange rates and the equity index in Ghana.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Dahir et al (2018) observed similar asymmetry across the BRICS countries, with positive impacts in Brazil and Russia, negative impacts in India, and a bidirectional relationship in South Africa. Gokmenoglu et al (2021) and Umoru et al (2023) also suggest that the response of stock returns to exchange rate fluctuations is not uniform in emerging economies and in oil-producing African countries, respectively. Amewu et al (2022) observed that the Covid-19 pandemic significantly altered the relationship between exchange rates and the equity index in Ghana.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gokmenoglu et al. (2021) and Umoru et al. (2023) also suggest that the response of stock returns to exchange rate fluctuations is not uniform in emerging economies and in oil-producing African countries, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation